Pengaruh Budaya Barat dalam Dinamika Perkembangan Cerpen Mesir - Fariz, Ilman; Ibad, Ahmad Ibnu (Universitas Al Azhar Indonesia, 2024)
This article discusses the dynamics of the development of Arabic short stories in Egypt. The research aims to explore the influence of Western culture on the evolution of short stories in Egypt. This is based on the fact that Arabic short stories, particularly in Egypt, have a unique development history compared to other literary forms. Before reaching their ideal form as known today, Arabic short stories existed primarily as maqamat. With the introduction of Western culture, the development of short stories progressed rapidly. This research employed a descriptive qualitative methodology by using a literature review approach. The data analysis process in this study consists of three stages: reduction, discussion, and conclusion. The results of this study are as follows: first, the short story is a relatively new form of prose in the Arab world. Second, the themes of Arab short stories, especially in Egypt, often focus on social issues. Third, the language style of short story writer is a blend of Fusha and 'Amiyah. Fourth, the influence of Western literary genres such as realism, surrealism, and romanticism in Arabic short stories. This influence can be traced in the works of Egyptian short story writers. Fifth, political-colonial and economic factors are among the main reasons for the influence of the West in Arabic literature.Keywords – Arabic Short Story, Development, Western Culture.